Discovery of a new quasar: SDSS J022155.26‐064916.6. Issue 5 (14th June 2017) - Robertson, J. M.; Tucker, D. L.; Smith, J. A.; Wester, W.; Lin, H.; Mueller, J. H.; Gulledge, D. J.
Abstract : We report the discovery of a new quasar: SDSS J022155.26‐064916.6. This object was discovered while reducing the spectra of a sample of stars being considered as spectrophotometric standards for the Dark Energy Survey. The flux‐ and wavelength‐calibrated spectrum is presented with four spectral lines identified. From these lines, the redshift is determined to be z ≈0.806. In addition, the rest‐frame u ‐, g ‐, and r ‐band luminosity, determined using a k ‐correction obtained with synthetic photometry of a proxy quasi stellar object (QSO), are reported as 7.496×10 13 L ⊙, 2.049×10 13 L ⊙, and 1.896×10 13 L ⊙, respectively.